2019
DOI: 10.1021/acschembio.9b00102
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Synthetic Acylation of a Target Protein in Living Cells Promoted by a Chemical Catalyst/Donor System

Abstract: Cell biology is tightly regulated by post-translational modifications of proteins. Methods to modulate post-translational modifications in living cells without relying on enzymes or genetic manipulation are, however, largely underexplored. We previously reported that a chemical catalyst (DSH) conjugated with a nucleosome-binding ligand can activate an acyl-CoA and promote site-selective lysine acylation of histones in test tubes. In-cell acylation by this catalyst system is challenging, however, mainly due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…We used two types of LANA-DSH catalysts, LANA 5-15 -DSH 1 and LANA 5-22 -DSH 2, and NAC-Ac 3 as a cell-permeable acetyl donor (Figure 1b). 12 As reported previously, 10 these catalysts efficiently promoted acetylation of H2BK120 in recombinant nucleosomes ( Figure S1). However, we could not detect H2BK120 acetylation by the catalyst system in living cells.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…We used two types of LANA-DSH catalysts, LANA 5-15 -DSH 1 and LANA 5-22 -DSH 2, and NAC-Ac 3 as a cell-permeable acetyl donor (Figure 1b). 12 As reported previously, 10 these catalysts efficiently promoted acetylation of H2BK120 in recombinant nucleosomes ( Figure S1). However, we could not detect H2BK120 acetylation by the catalyst system in living cells.…”
supporting
confidence: 73%
“…We then synthesized chemical catalysts conjugated with PEG-LANA ligands (Figure 3a). As the catalyst moiety, we used DSSMe, a pro-drugged DSH catalyst, 12 which is reduced to the active DSH form by biocompatible reductants, such as glutathione (GSH) or tris(2-carboxyethyl)phosphine (TCEP), prior to the reaction. The acetylation activity of the three catalysts (PEG 550 -LANA-DSSMe 11, PEG 750 -LANA-DSSMe 12, and PEG 2000 -LANA-DSSMe 13) was first examined in test tubes containing recombinant nucleosomes as substrates.…”
mentioning
confidence: 99%
“…In another principally similar report, biotin‐tethered diazotransfer reagent binds selectively to a protein for modification of a proximal lysine residue . Kanai and co‐workers demonstrated the efficacy of trimethoprim‐tethered nucleophilic catalyst for selective targeting of eDHFR in living cells . Also, Li and co‐workers reported sulfonium tethered peptide‐ligand directed modification of a Cys .…”
Section: Single‐site Labeling Of Native Proteinsmentioning
confidence: 94%
“…[121] Kanai and coworkers demonstrated the efficacy of trimethoprim-tethered nucleophilic catalyst for selective targeting of eDHFR in living cells. [122] Also, Li and co-workers reported sulfonium tethered peptide-ligand directed modification of a Cys. [123] Ball and coworkers demonstrated that a metallopeptide could provide proximity-driven catalysis for site-selective labeling of a protein.…”
Section: Ligand Directed Modificationsmentioning
confidence: 99%
“…1A). In contrast to the oligoDMAP-based catalysts, ligand-conjugated DSH catalysts can acetylate target proteins in living cells when the ligands are stable and functional in the cells (14). Biologically significant protein acetylation in living cells, such as histone acetylation, however, was not achieved yet.…”
mentioning
confidence: 99%